Fine-needle aspiration cytology of thyroid nodule(s) at a tertiary hospital in West Bengal, India: A 5-year experience - Krishnendu Das; Mausumi Basu; Susmita Sarkar; Sita Chatterjee (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2020)
Introduction: Thyroid nodules are a common clinical finding which is important due to their malignant potential. Fine-needle aspiration cytology (FNAC) is routinely used for first-line diagnosis of thyroid lesions and to differentiate benign from malignant nodules. Objective: The objective was to evaluate the advantage of FNAC as a simple procedure for the diagnosis of thyroid swelling. Materials and Methods: This is a retrospective study conducted at the department of pathology of a tertiary care hospital among 681 diagnosed patients of thyroid swelling who underwent FNAC. The results were interpreted according to the Bethesda nomenclature. Results: The most common age group affected was 20–29 years (29.22%), female patients were 90.46% and that of males were 09.54%, benign cases constituted 91.63%, follicular lesion of undetermined significance were 00.33%, follicular neoplasm were 02.93%, suspicious cases were 00.44%, malignant cases were 4.40%, and unsatisfactory were 00.33%). Among benign group, 45.03% of cases were of colloid goiter and 23.72% were of Hashimoto's thyroiditis. The malignant diagnoses yielded 83.33% of papillary carcinoma, 10% of medullary carcinoma, and 3.33% of anaplastic carcinoma. Conclusion: FNAC is a rapid and cost-effective screening test for accurate diagnosis of thyroid swellings.